Maternal outcome in antepartum eclampsia caesarean versus vaginal delivery - Behera, Nihar Ranjan; Patel, Jaiminkumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The term eclampsia is derived from a Greek word, meaning "like a flash of lightening". The onset of convulsions in a woman with pre-eclampsia that cannot be attributed to other causes is termed eclampsia. Eclampsia is an obstetric enigma. Though it has almost been eradicated from the developed world, it continues to be a major cause of maternal and fetal mortality and morbidity in the developing countries. The real challenge of eclampsia has not been met. In spite of considerable progress made in the field of obstetrics, the incidence of eclampsia and its consequent complications has not decreased significantly in our country over the past few decades. It is indeed sad that even today antenatal care is available only to a fraction of our rural population. However, the management of eclampsia still poses a fascinating challenge to the obstetrician, requiring the greatest skill, judgement and patience. Methods: This is an observational and prospective study of 200 cases admitted with eclampsia in MKCG medical college. The study was extended from October 2015 to September 2017. The inclusion criteria were antepartum eclampsia, primigravida and multigravida, duration of gestation>28 weeks. Patients with pregnancy & convulsion attributed to epilepsy or other causes were excluded from the study. Results: Of the 200 cases, caesarean section was done in 51.50% of the cases, while vaginal delivery was carried out in 48.5% of the cases. It was observed the caesarean section was having better maternal outcome than vaginal delivery. Conclusions: In antepartum eclampsia in primigravidas with more than 28 weeks gestation with unfavorable cervix on admission, an early decision for caesarean section either within 6 hours of admission or 12 hours of first fit whichever is earlier is paramount in improving the maternal outcome”. Prompt termination of pregnancy by caesarean section reduces maternal mortality, improves maternal outcome by reducing complications.